The rise of neoliberal philosophy human capital, profitable knowledge, and the love of wisdom - Absher, Brandon (Lexington Books, 2021)
"Brandon Absher demonstrates that the neoliberalization of higher education has led to a paradigm shift in contemporary philosophy in the United States. Neoliberal philosophy aims to produce human capital and profitable knowledge"--